Studi Tentang Tingkat Kesegaran Jasmani Mahasiswa Penjaskes STKIP PGRI Lubuklinggau - Azizil Fikri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine how the level of physical fitness students Penjaskes STKIP PGRI Lubuklinggau. The type of this research is descriptive that is to describe, express, and to get data related to physical fitness level of student of Penjaskes. Population of this research is student of Penjaskes force of 2016 as many as 18 people which conducted in environment campus STKIP PGRI Lubuklinggau. Technique of collecting data of this research is by test and measurement. To measure the level of physical fitness of students Penjaskes STKIP PGRI Lubuklinggau used 2.4 km cooper test run. Data analysis technique used is percentage analysis technique. The results stated that 8 people 44.44 percent had very good physical fitness. 6 people 33.33 percent have good physical fitness, 4 people 22.22 percent have less physical fitness level, whereas they have less physical fitness and less than none 0,00 percent Keywords: Physical Freshness, Student Penjaskes